Pharmacological Activity of Trachyspermum ammi L. Seeds Essential Oil Grown from Northeast India. Issue 6 (2nd November 2021) - Dutta, Pompy; Sarma, Neelav; Saikia, Samarjit; Gogoi, Roktim; Begum, Twahira; Lal, Mohan
Abstract: The present work has been aimed to investigate the chemical composition of the essential oil of Trachyspermum ammi L., seeds by gas chromatography/mass spectrometry method (GC/MS), antioxidant activity by DPPH, ABTS radical scavenging, reducing power assay; anti-inflammatory investigation using protein denaturation assay and anti-diabetic activity using the α-amylase inhibitory assay. The essential oil was further evaluated for antibacterial activity against various gram-positive bacteria Bacillus cereus, Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus and Streptococcus mutans and gram-negative bacteria Salmonella typhimurium and Salmonella enterica and compared with the standard Ciprofloxacin. Again, the antifungal activity was investigated against Fusarium keratoplasticum, Aspergillus niger, Saccharomyces cereviaceae, Candida albicans and Aspergillus fumigatus and compared with the standard Fluconazole. The GC/MS analysis of Ajwain essential oil revealed the presence of thymol (50.43%) as the major compound followed by other minor and trace compounds. Ajwain essential oil showed better antioxidant activity than that of standard as revealed by DPPH radical scavenging assay with Ajwain essential oil IC50 3.09 μL/mL which was better performing than ascorbic acid with IC50 8.87 μL/mL. The IC50 value of 21.38 μL/mL was shown by Ajwain essential oil followed by ascorbic acid 79.13 μL/mL in ABTS assay. The in-vitro anti-inflammatory assay revealed Ajwain essential oil as a good candidate for strong natural inflammation inhibitory drug formulation with an IC50 value of 93.12 μL/mL in albumin denaturation assay. Significant α-amylase inhibitory activity was also reported with an IC50 = 22.02 μL/mL better than standard acarbose IC50 = 22.46 μL/mL. Weak antimicrobial activity was reported against all the thirteen tested bacterial and fungal strains. From all the aforementioned results it can be concluded that the presence of the polyphenolic compound thymol (50.43%) resulted in strong antioxidant, anti-inflammatory and anti-diabetic activities of Ajwain essential oil, which resembles the use of thymol in the future as natural, cost-effective and potential antioxidant, inflammation inhibitory and anti-diabetic precursor for drug formulation.